Effect of pressure changes in sliding contact - Deeva, Vera; Slobodyan, Stepan (International Journal of Engineering and Technology, 2018)
The sliding contact when the air together with wear particles flow in contact area between commutator and brush is considered. The dynamical interaction between two surfaces is probabilistic. The behaviour of space-time-varying process is described by the differential equations, which are generally very difficult to solve. The simple numerical solution applying the method of Galerkin approximation to estimate the change in the pressure field in thin contact layer is obtained. It was found that under the leading edge of the brush the pressure change doesnâ€™t exceed 0.07 of the maximum value. The numerical simulations of the absolute error are presented for the 0.1, 0.2, 0.5, and 1 of the relative length. The relative error of pressure changes for small contact area is smaller (1Â â€“Â 0.8eÂ 0.1Ï„). It is concluded that the approximate solution tends to the exact one. Moreover, it is shown that as the sliding velocity decreases, the relative error of the pressure change tends to the zero.Â Â